The situation of work-related COVID-19 infection and Occupational Health and Safety measures in Thailand - Siriruttanapruk, Somkiat; Sansilapin, Chalo; Weeracharoen, Rachaneekorn; Tanathitikorn, Chuleekorn; Chaifoo, Walairat (European Journal of Oncology and Environmental Health, 2023)
Introduction: The pandemic of COVID-19 infection is the worst public health problem worldwide. Globally, most of cases are among working population. The aims of this study are to describe the situation of work-related disease in Thailand and currently implemented preventive and control measures. Methods: The data from the Situation Awareness Team under the Department of Disease Control (DDC) were collected and analysed in September 2020. The Monitoring and Evaluation Team under DDC also conducted a rapid survey to identify any measures enterprises had implemented to protect their employees from the disease. The checklists were applied from the ILO guideline. The survey was conducted via an on-line questionnaire using Google Form and sent to enterprises and the network of safety officers during 13th -17th April 2020. Fisher’s Exact test with p-value was used to compare the percentage of enterprises reported implementation of measures. Results: Until the end of September, total cumulative number of COVID-19 infection in Thailand were 3,519 cases (approximately 5.29 per 100,000 populations) and 2,445 cases (69.5%) were domestic infection. Among this group, 2,258 persons (92.4%) were working population, aged 18-60 years. 484 domestic cases (21.4%) were classified as work-related COVID-19 infection. The highest number of work-related infection (122 cases) were among workers who worked in entertainment sector. Regarding the calculation for proportions of number of work-related infection and total number of infected cases in each occupation, almost drivers got infection from their jobs. Other high risk occupations included masseurs (90.9%), flight attendants (87.5%), priests (all religions) (80.0%), and airport staff (78.6%). Regarding the rapid survey, 101 samples responded. Almost all enterprises reported having a policy and implementation of preventive and control measures. Implemented measures included health screening of their workers (97%), work arrangement, e.g., work from home (75.2%), area arrangement for work/social distancing (81.2%), ventilation improvement (59.4%), and provision of masks (100%). Conclusions: Most of domestic COVID-19 infection were among working age. Approximately one-fifth of them got infection from work. Occupations, especially working with or contact with foreigners and working in a high density of people, were high-risk factors. Several enterprises had implemented preventive and control measures. Prompt policy advocacy, knowledge-based recommendations and communication with target groups were essential.